Editorial – From paradox to practice: the rise of coopetition strategies. (1st January 2014) - Czakon, Wojciech; Fernandez, Anne-Sophie; Minà, Anna
What is a paradox? What are the consequences of naming a paradox for the actors involved in it? Coopetition strategies, defined as simultaneous competition and collaboration relationships between the same actors, represent a major paradoxical situation. Because of their paradoxical nature, coopetition strategies recently became an essential challenge for conceptualising a studied reality, but also for those who are experiencing the paradox as well. This special issue aims to contribute to the development of coopetition theory in shedding new light on the paradoxical nature of coopetition strategies. The questioning is mainly related to the definition of the concept, the appropriate level of analysis and the implementation of the coopetition process. The selection of articles focuses on the inner heterogeneity of coopetition, on the tensions arising while implementing coopetition process, and on the outcomes. They provide core operational and managerial insights.